Thyroid hormones-membrane interaction: Reversible association of hormones with organized phospholipids with changes in fluidity and dipole potential - Isse, Blanca Alicia de Los Angeles G. (2013)
Differential scanning calorimetry (DSC), mixed monomolecular layers and fluorescence spectroscopy techniques were applied to investigate the effect of thyroid hormones (THs) on the biophysical properties of model membranes. We found that both 3,3′,5-triiodo-l-thyronine (T3) and 3,5,3′,5′-tetraiodo-l-thyronine (T4) induce a broadening of the calorimetric main phase transition profile and reduce the transition enthalpy in liquid-crystalline state of dipalmitoylphosphatylcholine (DPPC) multilamellar vesicles. Tm changes from 41 °C to 40 °C compared to pure DPPC. When the experiments were done by adding THs to preformed multilamellar vesicles a second broader component in the DSC scan also appears at 20 min of incubation and becomes gradually more prominent with time, indicating a progressive alteration of lipid phase induced by THs. Analysis of surface pressure-molecular area isotherms in mixed monolayers of THs with either DPPC or 1-palmitoyl-2-oleoylphosphatidylcholine (POPC) at air–water interface indicated a reduction in molecular area for THs/lipid mixtures at all surface pressures. A substantial decrease in surface potential in mixed lipid/THs monolayers at all surface pressures were observed for both phospholipids without affecting the mixed monolayer integrity. The data of mixed lipid/THs behavior support the establishment of lateral miscibility. Alterations of bidimensional liquid expanded → liquid condensed phase transition observed for DPPC/THs mixed monolayers are compatible with the changes observed in DSC. The transverse movement of THs and the decrease of dipole potential were also observed in single unilamellar vesicles by using appropriate fluorescent probes.